Optimal carbon leakage - Topi Hokkanen (Bank of Finland, 2023)
Carbon leakage is one of the major issues facing policymakers today when designing environmental regulation. While the empirical and trade literature on carbon leakage is rich, much less is known about the implications of carbon leakage risk on optimal regulatory policies under asymmetric information. To this end, I derive the optimal incentive compatible mechanism to regulate polluting firms under asymmetric information of both their abatement costs and carbon leakage risk, which I model as type-dependent outside options. The resulting regulatory distortions depend on the affiliation between the firm's abatement and relocation costs. The optimal policy is less strict than first-best whenever this affiliation is negative or mildly positive, whereas under strong positive affiliation I find a novel upwards distortion in the optimal policy. My results imply that rather than being a byproduct of unsuccessful regulation, carbon leakage may be the optimally induced outcome of incentive compatible regulation, contrasting with the received wisdom in policy debate.
Keywords: D62; D82; L51; Q54; Q58; 330; carbon leakage; mechanism design; externalities; asymmetric information